The Role of German Guarantee Banks in Creating Harmonious Development of SME Companies - Dąbkowska, Anna (Journal of Finance and Financial Law, 2023)
The article attempts to examine the role of guarantee banks, whose main objective is to support the development of the competitiveness of SMEs by enabling them to access credit through the granted guarantee, in creating the harmonious development of enterprises in this sector The first part of the article presents the profile of guarantee banks in Germany and their added value for the economy. In the empirical part, based on data taken from Verband Deutscher Bürgschaftsbanken e.V. their participation in supporting the development of enterprises from the SME sector in the period before and during the COVID-19 pandemic was presented. The analysis shows that guarantee banks increase operational efficiency and contribute to reducing information asymmetry, specializing in credit assessment of enterprises (qualitative rather than quantitative), and at the same time reducing the financial gap. Their activities also have a positive impact on credit institutions, because they take on a large part of the risk. Thanks to their activities, there is a favorable climate in Germany for establishing new enterprises, whose only capital is "specialized know-how" and an innovative venture.